A escolha, o comprometimento e o entrincheiramento com a carreira e a área de atuação: um estudo entre administradores - Tonin, Stefania (2014)
The work can be seen by the individual as a job or as a career. Emmerling and Cherniss (2003) say that the choice of career/area of performance can not be taken under an isolated perspective, but the community of a series of decisions involving the individual levels of professional and personal aspirations. Thus, understanding the dynamics that embraces choice, and the bonds established with the career and area of performance, both individual and collective point of view, becomes significant, since a profession achieve its social statement if the individuals that composes it demonstrate commitment and dedication. Among the bonds formed by the individual are commitment and entrenchment. To Baiochhi and Magalhães (2004), these constructs are geared to explain the intention of the employee to remain on a course of action that defines his occupation and the investments that it makes. Therefore, this work was made whit the purpose to analyze how the choices about career and area of performance influence the relationships of commitment and entrenchment of the managers surveyed. It was conducted a descriptive study with a quantitative approach. Study participants totaled 208 administrators logged in Regional Management Board of Rio Grande do Sul (CRA-RS). A semi-structured questionnaire was applied, consisting of questions covering the respondents profile, the process of career choice and area of performance from Carvalho (2007) and about the bonds of commitment from Blau (1985) and Meyer and Allen (1984) and entrenchment from Carson et al (1995) with the career and area of performance. Data obtained were analyzed using descriptive statistics, nonparametric tests and correlations. It was evident that the administrators participants of the survey were predominantly male (52.88%), married (46.63%) with a mean age of 34 years. It was found that the process of career choice performed by administrators gave up predominantly by internal factors (45.94%), while the process of choosing the area of performance was guided by external factors (48.56%). In general, rates of commitment were more expressive than the levels achieved by the entrenchment bond, for career and area of performance. Correlations the bonds with the career and area of performance were significant and positive. However, the correlations between the choice process and the bonds, not reach significance, thus the study hypotheses were rejected. Finally, it is expected that this survey will serve to the better understanding of the administrator profession and how this professional form and establishes its bonds with the career and area of performance.